Processing of four different cooking methods of Oudemansiella radicata: Effects on in vitro bioaccessibility of nutrients and antioxidant activity. (1st February 2021) - Liu, Yuntao; Li, Yiwen; Ke, Yu; Li, Cheng; Zhang, Zhiqing; Liu, Aiping; Luo, Qingying; Lin, Bokun; He, Jialiang; Wu, Wenjuan
Graphical abstract: Highlights: The particle size of swallowing was mainly distributed at 4 mm. After digestion, the amino acid release (%) and DH% of steaming were highest. Fatty acid composition was significantly changed after digestion. The bioaccessibility of minerals was slightly affected by the cooking method. Antioxidant activity was demonstrated to varying degrees in the four groups. Abstract: The purpose of this study is to evaluate the bioaccessibility of nutrients and antioxidant activity of O. radicata after subjecting to four types of domestic cooking and followed by in vitro digestion. The result demonstrated that the group with the lowest amino acid release and the degree of protein hydrolysis (5.6%) was frying, but both reducing sugar content and antioxidant activity were the highest. The composition of fatty acids was different than undigested samples, especially the relative content of linolenic acid was significantly decreased (e.g., 34.49 to 8.23%, boiled). The difference of the minerals bioaccessibility was slightly affected by the cooking method, but mainly related to their natural properties, such as the highest phosphorus (62.73%) and the lowest iron (21.53%) in the steaming. The above data provides a starting point for the design of processes at an industrial and gastronomic level.